Applications of Mesenchymal Stem Cells in Liver Fibrosis: Novel Strategies, Mechanisms, and Clinical Practice - Mengmei Zhu; Tianzhen Hua; Tao Ouyang; Huofu Qian; Bing Yu (Hindawi Limited, 2021)
Liver fibrosis is a common result of most chronic liver diseases, and advanced fibrosis often leads to cirrhosis. Currently, there is no effective treatment for liver cirrhosis except liver transplantation. Therefore, it is important to carry out antifibrosis treatment to reverse liver damage in the early stage of liver fibrosis. Mesenchymal stem cells (MSCs) are the most widely used stem cells in the field of regenerative medicine. The preclinical and clinical research results of MSCs in the treatment of liver fibrosis and cirrhosis show that MSC administration is a promising treatment for liver fibrosis and cirrhosis. MSCs reverse liver fibrosis and increase liver function mainly through differentiation into hepatocytes, immune regulation, secretion of cytokines and other nutritional factors, reduction of hepatocyte apoptosis, and promotion of hepatocyte regeneration. Recently, many studies provided a variety of new methods and strategies to improve the effect of MSCs in the treatment of liver fibrosis. In this review, we summarized the current effective methods and strategies and their potential mechanisms of MSCs in the treatment of liver fibrosis, as well as the current research progress in clinical practice. We expect to achieve complete reversal of liver injury with MSC-based therapy in the future.